Tarif Angkutan Umum Pada Masa Pandemi Covid 19 - Syarifah Aini Nasution; Zul Anwar Azim Harahap; Sawaluddin Siregar (IAIN Padangsidimpuan, 2021)
This research is motivated by the determination of public transportation fares, hereinafter referred to as city transportation, the application of tariffs during the Covid 19 Pandemic is still carried out by means of deliberation between ORGANDA and car owners, which in the implementation of leasing between car drivers and passengers, there are often inconsistencies with regulations. The main problem in this study is how to apply public transport fares during the Covid 19 Pandemic in Padangsidimpuan City and how to review muamalah fiqh on the application of public transport fares during the Covid 19 pandemic. This study uses a field research method and is sourced from primary and secondary data. Data collection techniques used in this study were observation, interviews and documentation. The results showed that the application of the tariff carried out in the field by the driver was not in accordance with the tariff determination set by ORGANDA and the owner. Very often there is an increase in fares made by drivers to passengers for various reasons, such as the lack of passengers, and the absence of small change. So that not a few people feel uncomfortable with this behavior. According to the muamalah fiqh review of public transportation fares during the Covid 19 Pandemic in Padangsidimpuan City, it can be seen from the terms of ijarah, namely about the pleasure between the tenant and the renter, and there is no element of coercion from either of them. The decisions that have been made are not in accordance with the implementation carried out by the driver.